Legal system of residency and access to the Vatican City - SARAIS, ALESSIO (Prawo Kanoniczne, 2014)
On February 22 2011 Pope Benedict XVI promulgated a new Law concerning citizenship, residency and access to the Vatican City, n. CXXXI. This Law replaces the previous Law June 7 1929, n. II. Art. 9 of the Lateran Treaty deals also with this matter. According to the old Law of 1929 citizenship and residence were directly connected. A first derogation thereto ensued from a decision of Pope Pius XII in 1940: the Holy See diplomats, who actually did not have their residence in the Vatican City State, were nonetheless Vatican citizens. The new Law of 2011 distinguishes between Vatican citizens who are also resident in the Vatican City State, citizens who are not resident (for example members of the diplomatic corps) and finally residents who are not Vatican citizens (because they do not apply for or do not obtain the citizenship). The new Law provides for the requisites to obtain the residency in the Vatican City State even without citizenship: the enrolment in a special register and the issue of a personal card, which allows free access to the territory of the Vatican State. The new Law regulates as well the general conditions of access to the territory of the Vatican State for those who are not citizens of and have no residence in it. According to Art. 3 of the Lateran Treaty Saint Peter’s Square is ordinarily accessible to everyone, without any formality. Sanctions are to be applied in case of unauthorized access to the Vatican City State. Even in this matter of the residence and access the Vatican legal system safeguards the peculiarity of the Vatican State in view of protecting the freedom of the Pope and of the Holy See